EARLY CHILDHOOD IN TODAY’S FAMILY. THE CHRISTIAN LANDMARKS IN THE LIVES OF OUR CHILDREN - BRÂNZĂ, Mihaela (Studia Universitatis Babeș-Bolyai Theologia Orthodoxa, 2022)
Early childhood represents the most important developmental period. Parents are nowadays confronted with serious challenges in their educational strivings. Many young spouses choose to learn about child psychology to overcome the difficulties raised by a baby’s presence. Christian parents delineate their educational efforts by taking into consideration God’s commandments. Prayer and patience are combined so that a loving dialogue conducts all the family interactions. Pre-schoolers are extremely attentive to what their parents do every day. Their kind gestures and words form the child’s personality. Participation in the liturgical program of a church proves the authentic faith of the parents. Accustomed to the intense atmosphere of a dynamic ecclesial community, the Christian children are taught how to use theological teaching in their daily life. They learn important rules and limits about emotional reactions, expressing compassion, and loving their family, friends, and even strangers. The model provided by mum and dad always had a formative effect. Christian parents instil in their children the willingness to follow love, faith, and trust as the main virtues that a human being can hope for.